Blurring the Boundaries: Reflecting on PDS Roles and Responsibilities through Multiple Lenses - Lotta C. Larson; Amanda D. Lickteig; Vicki S. Sherbert; Deborah A. Nauerth (Educational Considerations, 2014)
It is well documented that successful Professional Development School (PDS) initiatives are contingent on trusting relationships between the university and school districts.
Keywords: partnership; responsibilities; roles; benefits; PDS; challenges; teachers; students; collaboration